Factors In The Affrication Of The Ejective Alveolar Fricative In Tigrinya - Moeng, Emily; Carter, William (My University, 2019)
Ejective fricatives are typologically rare sounds, attributable to the fact that they present an articulatory dilemma with contrasting demands for their fricative and ejective components. Several articulatory coping mechanisms have been observed across languages (Maddieson 1997; 1998). In the case of Tigrinya, Shosted & Rose (2011) find that the ejective alveolar fricative, /s’/, is affricated more often than not (/s’/ produced as [ts’]), proposing affrication to be another possible coping mechanism. This study assesses two possible factors affecting the rate or degree of affrication in Tigrinya: 1) the vowel environment surrounding /s’/ and 2) the lexical frequency of words containing /s’/. While we find no effect of lexical frequency, we find a significant effect of vowel context, with the lowest rate of affrication occurring following [i] and preceding [u]. We propose that this finding suggests that this environment, naturally aids the production of ejective fricatives due to vowel coarticulation, as the decreasing supralaryngeal volume over the duration of the fricative counteracts the loss of air due to frication.
Keywords: Tigrinya; Ejective fricative; languages